Developments in optical imaging for gastrointestinal surgery. (November 2017) - Upchurch, Emma; Griffiths, Shelly; Lloyd, Gavin-Rhys; Isabelle, Martin; Kendall, Catherine; Barr, Hugh
To improve outcomes for patients with cancer, in terms of both survival and a reduction in the morbidity and mortality that results from surgical resection and treatment, there are two main areas that require improvement. Accurate early diagnosis of the cancer, at a stage where curative and, ideally, minimally invasive treatment is achievable, is desired as well as identification of tumor margins, lymphatic and distant disease, enabling complete, but not unnecessarily extensive, resection. Optical imaging is making progress in achieving these aims. This review discusses the principles of optical imaging, focusing on fluorescence and spectroscopy, and the current research that is underway in GI tract carcinomas.